Spectral domain optical coherence tomography for higher precision in the evaluation of vitreoretinal adhesions in exudative age-related macular degeneration. Issue 10 (26th January 2011) - Krebs, Ilse; Glittenberg, Carl; Zeiler, Florian; Binder, Susanne
Abstract : Aim: The role of changes at the vitreoretinal interface and vitreomacular traction forces in pathogenesis, and the course of exudative age-related macular degeneration (AMD) need further exploration. This study examines the localisation of adhesion and the direction of traction lines in eyes with exudative AMD. Methods: The cubes 512×128 of Cirrus optical coherence tomography (OCT) and volume scans of Spectralis OCT were reviewed in a consecutive series of patients presenting between December 2008 and March 2009 with vitreomacular adhesion in exudative AMD. Results: 30 eyes of 25 patients with exudative AMD and vitreomacular adhesion were studied. 50% had type III lesions, 46.7% occult and 3.3% predominantly classic lesions. The localisation of the adhesion corresponded in 100% with the area of the neovascularisation (CNV), in 73.3% traction directed towards the CNV and in 83.3% towards the optic disc could be noted. Spectral domain OCT and 3D visualisation enabled clearer localisation of vitreomacular adhesion and definition of resulting traction lines. Conclusion: There is a high prevalence of type III lesions within eyes with vitreomacular adhesions, and complete correspondence between the location of the adhesion and the CNV. There is also a high incidence of vitreopapillary adhesion in these cases, suggesting a possible role in pathogenesis.